Implementasi Metode Complex Proportional Asessment (COPRAS) Pada Sistem Pendukung Keputusan Pemilihan Bluetooth Audio Transmitter - Dedy Alamsyah; Rini Nuraini; Muhammad Bagir (Journal of Computer System and Informatics (JoSYC), 2022)
Bluetooth audio transmitter is a device capable of converting wired audio signals into wireless. With a Bluetooth audio transmitter, a TV or PC that doesn't have bluetooth facilities can connect to headphones or speakers without using a cable. However, currently bluetooth audio transmitters have been circulating in the market with various brands and brands that offer different capabilities and specifications. So, it takes foresight in choosing the right bluetooth audio transmitter and as needed. Inaccuracy in choosing a bluetooth audio transmitter results in the device's performance not being maximized and incompatibility with the wishes of the user. This study aims to develop a decision support system for selecting a bluetooth audio transmitter using the Complex Proportional Assessment (COPRAS) approach. The COPRAS method is able to solve election problems through the calculation of the utility level which shows the extent to which an alternative is better or worse than other alternatives through a comparison process. The system built has features such as managing criteria data, determining weights, managing alternatives, assigning a value to each alternative, seeing the results of the COPRAS method calculations and seeing the ranking of the results of the system recommendations. Based on testing through the black-box testing technique, it shows that the system built has been running as it should